Clinical round: 27 year old patient with initially diagnosed Crohn's disease and severe protein and energy deficiency - V. S. Scherbakha; O. Z. Okhlobystina; A. V. Korolev; O. S. Shifrin; A. V. Stepanov; A. S. Tertychny; A. V. Okhlobystin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of case presentation. To demonstrate the course of inflammatory and sclerosing variant of the Crohn’s disease, complicated by severe nutritional failure. Nonetheless good therapeutic response was achieved at combined anti-cytokine therapy with immunosuppressive drugs and adequate nutritional support. Summary. Disease manifested with diarrhea, general weakness, high fever, abdominal pain and significant weight loss. Laboratory tests demonstrated elevation of ESR and C-reactive protein and anemia. Patient was diagnosed as having irritable bowel syndrome in local hospital and received symptomatic treatment for one year. Later on patient underwent examination to exclude hematological disorder. In 1.5 years before admission to Vasilenko clinic of Sechenov University patient lost 30 kg of body weight. The diagnosis of Crohn’s disease in our clinic was established on the basis of careful study of clinical course of disease (late postprandial pain, diarrhea, fever and progressive weight loss). The diagnostic concept was confirmed by modern laboratory and instrumental methods of investigation (CT enterocolonography, endoscopic and histological study). Evaluation of nutritional status revealed the presence of protein-energy malnutrition of severe degree of alimentary marasmus type. Taking into account severe manifestations of a nutritional failure along with baseline therapy of autoimmune process at Crohn's disease (corticosteroids, immunosuppressors added by anticytokine therapy) patients received nutritional support that allowed to achieve clinical remission. Conclusion. Progression of Crohn’s disease with involvement of terminal ileum can result in proteinenergy malnutrition. Management of relapse of Crohn's disease and severe protein-energy malnutrition require nutritional support already at initial treatment stages